The effect of copper on the redox behaviour of iron oxide for chemical-looping hydrogen production probed by in situ X-ray absorption spectroscopy. Issue 18 (26th April 2018) - Yüzbasi, Nur Sena; Abdala, Paula M.; Imtiaz, Qasim; Kim, Sung Min; Kierzkowska, Agnieszka M.; Armutlulu, Andac; van Beek, Wouter; Müller, Christoph R.
Abstract : We report the influence of copper on the reduction rate and pathways of iron oxide based oxygen carriers for a chemical looping based H2 production cycle. Abstract : The production of high purity hydrogen with the simultaneous capture of CO2, can be achieved through a chemical looping (CL) cycle relying on an iron oxide-based oxygen carrier. Indeed, the availability of active and cyclically stable oxygen carriers is a key criterion for the practical implementation of this technology. In this regard, improving our understanding of the reduction pathway(s) of iron-based oxygen carriers and the development of concepts to increase the reduction kinetics are important aspects. The aim of this work is to evaluate the effect of the addition of copper on the redox behaviour of iron oxide based oxygen carriers stabilized on ZrO2 . In situ pulsed-H2 XANES (Fe K-edge) experiments allowed for the determination of the reduction pathways in these materials, viz. the reduction of both Fe2 O3 and CuFe2 O4 proceeded via a Fe 2+ intermediate: Fe2 O3 (CuFe2 O4 ) → Fe3 O4 (Cu 0 ) → FeO (Cu 0 ) → Fe 0 (Cu 0 ). In the first step CuFe2 O4 is reduced to Cu 0 and Fe3 O4, whereby Cu 0 promotes the further reduction of iron oxide, increasing their rate of formation. In particular, the rate of reduction of FeO → Fe 0 is accelerated most dramatically by Cu 0 . This is an encouraging result as the FeO → Fe 0 transition is the slowest reduction reaction.